Organization development fundamentals : managing strategic change - Rothwell, William J., 1951- (ATD Press, 2015)
In a tumultuous global business environment, change is a constant. Organizations are affected by many factors from the local economy to global competition. To be successful they must do more than react to changes, they need to be proactive. Organization Development Fundamentals provides a starting point for those interested in learning more about taking this proactive approach. The authors explore the many facets of organization development and change management, including the theories, models, and steps necessary to complete the process. This is a perfect resource for professionals who are just starting out in the OD field or who want to brush-up on the basics. After reading this book, you will be able to: Define organization development and change management. Implement a change effort. Understand the competencies required of successful change agents. Recognize and solve ethical dilemmas related to change.